Cross‐Border Social Dumping as a 'Game of Jurisdiction' – Towards a Legal Geography of Labour Relations in the EU Internal Market. (4th February 2021) - Iossa, Andrea; Persdotter, Maria
Abstract: The question of social dumping has again climbed the EU policy agenda. In this article, we call into question some established views of social dumping that conceptualize the relationship between EU internal market and Member States in binary terms. Based on an analysis of relevant case law, and drawing on the conceptual tools provided by critical legal geography, we show that the project of EU integration relies as much on the scalar differentiation of powers as it does on the 'upward' shift of powers from the national‐ to the supra‐national level. We propose an understanding of EU internal market law as productive of a 'labour law patchwork', defined by the simultaneous fragmentation and overlap of labour law regulations across and within EU Member States. Here, we re‐conceptualize cross‐border social dumping as a 'game of jurisdiction' – a set of strategic moves by actors within a multi‐scalar and multi‐jurisdictional space.